The Role of Baznas in Empowering MSMEs Through Productive Zakat in the City of Medan - Musliyani Musliyani; Marliyah Marliyah (Penerbit Jurnal Indonesia, 2022)
MSMEs have an important role in driving economic growth. However, MSMEs cannot be separated from the problems encountered when running a business that can affect the success of the business. These problems can be in the form of problems related to capital and non-capital that make it difficult for MSMEs to develop and transform into large-scale businesses. The National Amil Zakat Agency (BAZNAS) as an institution that manages zakat in Indonesia has funds that can be used as business capital or referred to as productive zakat. In this study, researchers observed how MSME empowerment activities were carried out by the Amil Zakat Agency using productive zakat funds in the city of Medan. This research uses qualitative analysis and descriptive approach, with secondary data sources. The results of the research found that BAZNAS North Sumatra has a program that is engaged in community economic empowerment, namely the North Sumatra Makmur program which in this program uses grant and qardhul hasan contracts. This program provides capital assistance, training, mentoring, coaching for mustahiq. The existence of the prosperous North Sumatra program has a positive impact on MSMEs as mustahiq who receive productive zakat. Stable economic conditions and an increase from a mustahiq to a muzakki are also a form of Baznas' success in empowering the community's MSMEs. Therefore, the role of BAZNAS North Sumatra in empowering MSMEs through productive zakat is sufficient to provide a better direction for change and lead to prosperity.